Prey species and prey selection of dholes at three different sites in Thailand - KHWANRUTAI CHARASPET; ronglarp - sukmasuang; NORASET KHOEWSREE; MANANYA PLA-ARD; YUWALUK CHANACHAI (Society for Indonesian Biodiversity, 2020)
Abstract. Charaspet K, Sukmasuang R, Khoewsree N, Pla-ard M, Chanachai Y. 2020. Prey species and prey selection of dholes at three different sites in Thailand. Biodiversitas 21: 5248-5262. The study of prey species and prey selection of Dholes at 3 different sites was conducted at Khao Yai National Park, Salak Pra, and Huai Kha Khaeng Wildlife Sanctuaries from 2013 to 2020. Information on Dhole prey at the sites was collected from the residues of dhole scats, from which the selection index, the relative biomass of the prey, and the relative amounts of the consumed prey were calculated. The data were collected simultaneously with the use of camera traps at each site. The study revealed that there were 13 species of Dhole prey with body weight over 5 kg. The result indicated that there were 7 species of even-toed ungulates. The relative biomass of even-toed ungulates ranged between 76.78 - 90.50% of the total biomass of all the Dholes’ consumed prey for all study sites. The dietary diversity index unveiled a similar index in all areas, which proved the adequacy of the analyzed scats. However, the Niche breadth index, which indicates the relevance of prey selection and prey species to the appearances of the prey at each site, was found to be high at Huai Kha Khaeng Wildlife Sanctuary, Khao Yai National Park, while the index was found to be low at Salak Pra Wildlife Sanctuary. The results revealed that Dholes consumed viverrid species and Malayan porcupine more often at the site where there were large carnivores. The recommendation from this study was the conservation and restoration of the ungulate populations, the main prey, as it greatly affects the conservation of the Dhole populations in Thailand.  Grassland and salt lick sites, water sources improvements are also important to promote prey population. The conservation of wildlife prey by releasing them to nature, as currently conducted, has an effect on the increase of Dholes’ prey species.